Coxiellaburnetii (Q fever) exposure in wildlife professionals - Danilo Alves de França; Louise Bach Kmetiuk; Orlei José Domingues Rodrigues; Giovanni Augusto Kalempa Panazzolo; Vivien Midori Morikawa; Ana Íris de Lima Duré; Helio Langoni; Giovani Marino Fávero; Alexander Welker Biondo; Alexander Welker Biondo (Frontiers Media S.A., 2024)
IntroductionAlthough occupational exposure to Coxiella burnetii has been studied previously, the zoonotic risk in wildlife environments remains unclear and has yet to be fully established.MethodsAccordingly, the present study aimed to serologically assess professionals with daily contact with free-living and captive wildlife in Paraná State, Brazil, along with the potential associated risk factors for C. burnetii exposure.ResultsOverall, 25 out of 309 (8.1%) wildlife professionals were seropositive, including 6/54 (11.1%) national and 7/125 (5.6%) state park employees, 6/92 (6.5%) zookeepers, and 6/38 (15.8%) animal service workers, with titers ranging from 32 to 128. No statistical association was found between seropositivity and associated risk factors, including the working location.DiscussionOur results differ from those of previous studies in Brazil, which found 8/893 (0.9%) indigenous, 1/18 (5.5%) police officers, and 44/200 (22.0%) former Black slaves to be seropositive. This study is the first serological investigation of C. burnetii among park rangers, zookeepers, and animal service workers in Brazil, showing no statistically significant risk factors for seropositivity. As the seroprevalence in this study was higher than that in previous surveys of healthy (asymptomatic) human populations, C. burnetii exposure may also be an occupational risk for wildlife professionals owing to their contact with the natural environment in Brazil.